EXTRACTION RELATIONAL DEPENDENCIES OF THE BUSINESS PROCESS USING THE ANALYSIS OF ITS LOG - Левикін, В. М.; Чала, О. В. (Science-based technologies, 2016)
Process management involves constructing business process models and further process control using of these models. The process model includes a series of actions to address the relevant functional task. This sequence may vary performers with personal knowledge of the context of the process. The context consists of interconnected objects; it interacts with the business process. Identifying of relationships between objects based on log analysis and further their inclusion in the model of the process is needed to improve the efficiency of process control. Structuring of business process objects is completed. The method of allocating the relational component of the knowledge of the business process by analyzing its log is proposed. The method identifies dependencies at the level of process objects and objects attributes and attributes values. The method provides the possibility of formalization and subsequent inclusion in the model elements of personal knowledge of the performers. These elements were used to change the course of a process, and then these changes are written to the log.